Communicating health advice on social media: A multimodal case study - Engebretsen, Martin (MedieKultur: Journal of media and communication research, 2023)
Social media represent new arenas for health communication. Platforms such as YouTube, Instagram, Snapchat, and TikTok provide unique opportunities for health workers to build understanding, engagement, and trust among a broad and young audience. At the same time, such platforms demand of health workers a careful balance between social closeness and professional distance. The article is based on a case study in which the award-winning Norwegian psychologist Maria Abrahamsen’s practice of health communication on Instagram is studied through the lens of multimodal discourse analysis. Following a bottom-up method, the study starts with a close reading of a single Instagram post, where video and written verbal text interact closely. The entire account is then studied as a complex case of mediated health communication. Conclusively, after a discussion of genre implications, the article suggests possible solutions to key challenges concerning the followers’ engagement and trust.